First record of the genus Oediceroides (Amphipoda: Amphilochidea: Oedicerotidae) for the Gulf of Mexico, with the description of a new species - Carlos Varela; Heather D. Bracken-Grissom (Novitates Caribaea, 2021)
The genus Oediceroides Stebbing, 1888 represents a group of 23 species of amphipods that live from shallow coastal areas to abyssal plains. Most of these species have been collected in deep waters from localities in the South Atlantic and Pacific Oceans, and only one species has been found in the Mediterranean Sea. Many oediceroids inhabit waters more than 200 meters deep with only four species confined to shallow waters. This is the first occasion in which a species belonging to the genus Oediceroides is recorded for the Gulf of Mexico. Here, we describe O. improvisus sp. nov., a species of marine deep-water amphipod collected in 925 meters of water. This species has carapace, mouthpart and pereopodal characters that unite it with other members of the genus. It differs from all other species due to unique rostral and pereopod seven characters, all discussed in detail further in this description. To date, only 20 deep-sea (>200 meters) benthic amphipods have been recorded in the Gulf of Mexico, in comparison with more than 200 species of shallow water representatives from the same region. Our study provides evidence that the deep waters of the Gulf of Mexico still hold undescribed biodiversity.